Importance of learning Global Health in strengthening Primary Health Care: an experience from Nepal - Yadav, Randhir Sagar; Shrestha, Shumneva (Health Prospect, 2019)
Global health is a multidisciplinary and interdisciplinary approach of dealing transnational determinants of health. Strengthening health care institutions is vital for achieving universal health care. It also favors global health outcomes as it bridges gaps of health inequalities and saves numerous lives. In Nepal, the Institute of Medicine, Tribhuvan University is offering global health course since 2013. This paper discusses practical application of the learnings from the global health course to make commendable achievements at a primary health center. The global health course can be the foundation for transforming clinicians and public health practitioners into promising global health leaders. This will contribute to improve basic health care services, quality care, and vaccination program to improve the health of population. Therefore, global health course should be an imperative of medical education to capacitate doctors working in these settings to better understand the social determinants of disease prevention, care and rehabilitation.